Technology Leveraging for Infrastructure Asset Management: Challenges and Opportunities - Aktan, A. Emin; Bartoli, Ivan; Karaman, S. Gokhan (Frontiers in Built Environment, 2019)
Transportation and other infrastructure systems, particularly in dense urban regions, are intertwined, interdependent, multi-scale, multi-domain and complex, and their behavior cannot be predicted even when element behaviors are known. Such systems should be managed just like financial assets, leveraging measurement-based, objective and reliable metrics for documenting their value, performance and condition, and based on their lifecycle and disutility risk for each distinct limit-states of performance as discussed in the following. In this paper writers attempt to offer a perspective for asset management of civil infrastructures with a focus on highway bridges and describe the tools that are considered necessary for rectifying the current shortcomings mainly arising from subjective and incomplete performance and condition evaluation practice. The adoption of sensing systems, which allows measurements of displacement, acceleration, strain, tilt and that can be collected wirelessly, has the potential of providing objective metrics needed for optimal asset management. The authors however caution that such a transition (from asset management based on visual inspection to data-driven asset management based on objective metrics) could be truly achieved only if combined with the proper training of a new generation of infrastructure inspectors and stakeholders. The paper attempts to provide a roadmap to achieve such a transition in asset management and describes the critical concepts that should be incorporated in training a new generation of civil engineers in charge of maintaining our transportation assets.